Portrayal of Muslim Images in International Newspaper’s Blogging Forums and Its Impact on Readers - Yasin, Zaeem; Dure Ajam; Waheed, Aqdas (Journal of Peace, Development and Communication, 2021)
Abstract This study explores the portrayal of Muslim image in the international newspaper’s blogging forums and its impact on readers. The objective prolongs to find out the online interpersonal relations between the individuals of Muslim religion with individuals of other religions and the consequences of propagation of negative Muslim image in the web blogging. For this purpose, Survey method was used to seek the impact on the targeted readers and Content analysis of the blogs encompassing six bloggers from two leading newspapers’ online edition. The study implies Propaganda Model and Agenda Setting Theory by Norm Chomsky (1988) & Max McCombs and Donald Shaw (1968) respectively. The study reveals that propagation of negative Muslim image is adversely affecting the relations of individuals in online communities and Muslims are deleteriously represented in the web blogs of international newspapers. Key words: Portrayal, Muslims, Blogging Forums